An integrative approach unveils FOSL1 as an oncogene vulnerability in KRAS-driven lung and pancreatic cancer - Adrian Vallejo (Nature Portfolio, 2017)
KRAS-driven cancers remain refractory to current clinical therapies. In this study, the authors show that lung and pancreatic cancers expressing oncogenic KRAS can be targeted by genetic inhibition of FOSL1, which involves downregulation of genes of the mitotic machinery.